Quality inspection of natural leather using non-destructive testing technique. Issue 4 (1st October 2020) - Chudzik, S.
ABSTRACT: Results of a novel method of testing natural, tanned hides, in particular full grains, for both internal and external structural defects are presented. Such defects may occur while the animal is still alive or during the hide tanning and finishing processes. The method, still under development, uses a specially designed lamp to produce a thermal excitation impulse and an infrared camera to measure the surface temperature distribution. A newly developed algorithm is employed to process a series of thermograms recorded while the natural leather surface is heated and cooled in turn. Presented are selected results of experimental investigations carried out both on a specially prepared sample and other specimens of natural leathers. The Matlab environment was used to carry out numerical calculations. The solution discussed here represents a part of the project aimed at developing an industrial device for detecting structural flaws of leathers used for luxury upholstered furniture.